Amyloid Beta Oligomers Target to Extracellular and Intracellular Neuronal Synaptic Proteins in Alzheimer's Disease - Ding, Yu; Zhao, Jiahui; Zhang, Xunle; Wang, Shanshan; Viola, Kirsten L.; Chow, Frances E.; Zhang, Yang; Lippa, Carol; Klein, William L.; Gong, Yuesong (Frontiers in Neurology, 2019)
Background: β-Amyloid protein (Aβ) putatively plays a seminal role in synaptic loss in Alzheimer’s disease (AD). While there is no consensus regarding the synaptic-relevant species of Aβ, it is known that Aβ oligomers (AβOs) are noticeably increased in the early stages of AD, localizing at or within the synapse. In cell and animal models, AβOs have been shown to attach to synapses and instigate synapse dysfunction and deterioration. To establish the pathological mechanism of synaptic loss in AD, it will be important to identify the synaptic targets to which AβOs attach. Methods: An unbiased approach using far western ligand blots has identified three synaptic proteins to which AβOs specifically attach. These proteins (p100, p140 and p260) were subsequently enriched by detergent extraction, ultracentrifugation, and CHT-HPLC column separation, and sequenced by LC-MS/MS. P100, p140 and p260 were identified. These levels of AβOs targets in human AD and aging frontal cortexes were analyzed by quantitative proteomics and western-blot. The polyclonal antibody to AβOs was developed and used to block the toxicity of AβOs. The data were analyzed with one-way analysis of variance. Results: AβOs binding proteins p100, p140 and p260 were identified as Na/K-ATPase, synGap and Shank3, respectively. α3-Na/K-ATPase, synGap and Shank3 proteins showed loss in the postsynaptic density (PSD) of human AD frontal cortex. In short term experiments, oligomers of Aβ inhibited Na/K-ATPase at the synapse. Na/K-ATPase activity was restored by an antibody specific for soluble forms of Aβ. α3-Na/K-ATPase protein and synaptic β-amyloid peptides were pulled down from human AD synapses by co-immunoprecipitation. Results suggest synaptic dysfunction in early stages of AD may stem from inhibition of Na/K-ATPase activity by Aβ oligomers, while later stages could hypothetically result from disrupted synapse structure involving the PSD proteins synGap and Shank3. Conclusion: We identified three AβO binding proteins as α3-Na/K-ATPase, synGap and Shank3. Soluble Aβ oligomers appear capable of attacking neurons via specific extracellular as well as intracellular synaptic proteins. Impact on these proteins hypothetically could lead to synaptic dysfunction and loss and could serve as novel therapeutic targets for AD treatment by antibodies or other agents.